1987
DOI: 10.1007/bf00389972
|View full text |Cite
|
Sign up to set email alerts
|

Does in vitro colony formation and chemosensitivity relate to DNA ploidy and S-phase fractions?

Abstract: In vitro colony formation and chemosensitivity were analyzed in 65 human solid tumors and compared to proliferation parameters simultaneously obtained by DNA flow cytometry of the same tumor specimens. Colony growth in the human tumor colony assay was enhanced in aneuploid tumors (39/65) in comparison to diploid tumors (26/65, P less than 0.05). In addition, there was a relationship between % S-phase and colony growth. The existence of polyploid sublines (23/65) improved in vitro growth even in tumors with a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1989
1989

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Results are equivocal concerning the clinical implications and prognostic values of the differences in ploidy. Some authors have found that ploidy differences correlate with increased aggressiveness of the disease and poorer prognosis following treatment (Volm et al, 1985;Preisler et al, 1983), but others have not (Masters et al, 1987;Flentje et al, 1987). In the present investigation, we explored the relationship between changes in ploidy and HzOz resistance.…”
Section: Discussionmentioning
confidence: 93%
“…Results are equivocal concerning the clinical implications and prognostic values of the differences in ploidy. Some authors have found that ploidy differences correlate with increased aggressiveness of the disease and poorer prognosis following treatment (Volm et al, 1985;Preisler et al, 1983), but others have not (Masters et al, 1987;Flentje et al, 1987). In the present investigation, we explored the relationship between changes in ploidy and HzOz resistance.…”
Section: Discussionmentioning
confidence: 93%